Síntese, caracterização e estudos termoanalíticos dos cloroacetatos de lantanídeos (III) com a 2-piperidinona - Motta, Marcus Vinícius Lisboa (2010)
This work was carried out the synthesis, characterization and studies thermoanalyticalofthe complexesofchloroacetates of the lanthanides (III) with the 2-piperidinone.The complexes were characterized and analyzedby complexometric titration with EDTA, elemental analysis, molecular conductivity, in the infrared spectroscopydata, in the visible absorption spectroof neodymium compound and thermal analysis (TG/DTG e DSC) for all compounds.The compounds are crystalline solids and slightly, soluble in water and dimethylformamide. Conductance measurements in the dimethylformamide indicate a non-eletrolytes behaviour.Infrared spectra showed shifts to lower frequencies of ?CO plus?assCOO. According to theshifts and splitting observed in the Infrared spectrawesuggest that the lactam isbonded through the carbonyl oxygen.The Oscilater Power from the electronic absorption of the solution neodymium compound, indicate poor interaction betweenelectronic transitions: 4I9/2? 2G7/2, 2G5/2 and 4I9/2? 2P1/2of the neodymium ion and dimethylformamide.Thermogravimetric curves (TG / DTG) reported that the complex when heated, undergo fusion without decomposition, except for the complex of neodymium, which presents decomposition during the fusion. The profile of the thermal decomposition of these complexes can be divided into two steps for all the complexes. Peaks have been observed in the DSC curves, with features endothermic and exothermic, related to the merger and decomposition of the complex